Investigation on the tribological properties of Al\(_2\)O\(_3\)-TiC substrates in fixed abrasive lapping for data storage applications - FERNANDEZ, Benjie Locsing; SRISUWAN, Thanakrit; TUNGASMITA, Duangamol; TUNGASMITA, Sukkaneste (Journal of Metals, Materials and Minerals, 2026)
Alumina titanium-carbide (Al2O3-TiC) or simply AlTiC substrates were widely used in the magnetic recording industry for their superior mechanical and tribological properties. This study investigated the effect of AlTiC substrate crystal structure, chemical bonding and grain size in slider fix abrasive lapping tribology. Two types of AlTiC substrates, Type-A AlTiC and Type-B AlTiC equipped with an electro lapping guide (ELG), fully functional reader and writer devices were used in the study. The type-B lower material removal rate resulting to rougher surface finish was mainly due weakening caused by the titanium oxycarbide phase, which was the dominant factor, outweighing the minimal contribution from grain-boundary strengthening (Hall-Petch effect). Furthermore, the grain size investigated in this study was between 420 nm to 670 nm, making it far too large for the inverse Hall–Petch effect which involves softening at exceedingly small grain sizes typically below 100nm to be a relevant mechanism. The findings also highlight the importance of lapping parameters optimization to balance material removal rate (process productivity and efficiency) and surface finish (magnetic head reliability and areal density performance).